Factors that influence global literacy: what is the most dominant? - Pratama, Anggi Tias; Sudrajat, Ahmad Kamal; Anazifa, Rizqa Devi; Kurniawati, Atik (Institute of Advanced Engineering and Science, 2024)
Global literacy is a crucial ability to maintain the world’s peace. Several studies show that demographic factors influence the development of a person’s competence. However, the influence of demographic factors on global literacy has not yet been explored, especially in high school students. This research was conducted to determine the factors that most influence students’ global literacy in biology learning. The factors used in this research are gender, school profile (public or private school), and interest in learning biology. This study used a cross-sectional survey design with 2,759 students participating. Students’ global literacy was analyzed from a questionnaire of four aspects: exploration, communication, using the internet, and act for society. This study found that all the proposed factors influence students’ global literacy, but the factor that has the most dominant influence is the school profile. This research provides a new view regarding the influence of demographic factors on students’ global literacy. The government and related parties can use these results to design effective learning innovations to develop students’ global literacy.